Simulasi Perancangan VANET Pada Jak Lingko Koridor 6 Transjakarta - Muhammad Ramiz Kamal; Primantara Hari Trisnawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
People who prefer to use private transportation are due to the lack of facilities provided to users of public transportation. In addition to the lack of facilities provided, many cases of public transportation have problems with delays in sending and receiving bus location data, for example TransJakarta. Delayed data is information that does not arrive according to the predetermined time, from the case of this data delay, the bus that arrives does not match the time displayed to the user. To fix delayed data, the Vehicular Ad-hoc Network (VANET) can be applied to public transportation. The application of VANET can assist in measuring delay and throughput from the Road Side Unit to the bus or vice versa. From the measurement results, information about the current location of the bus will be obtained, which will be sent to the user information page (Network Simulator). The implementation of VANET in this system uses a Network Simulator with the Ad Hoc on Demand Distance Vector (AODV) reactive routing protocol that forms a route from the source node to the destination node based on the source node request and communication using an antenna. From the test results, the average delay value obtained is 79.86 milliseconds (ms) with a minimum value of 0.009 seconds, and an average throughput value of 275.29 KB / s with a minimum value of 0 B / s. From the results obtained, the Vehicular Ad-Hoc Network (VANET) itself can guarantee the throughput and delay of a data transmission flow.